Swedish election study 1979 - Holmberg, Sören; Statistics Sweden (University of Gothenburg, 1984)
The Swedish election study 1979 was carried out in connection with the general election in September. Many of the questions are replications of questions asked in previous election studies. In this study the respondents specifies for each political party what they appreciates and what they dislikes with the party´s policy. There is also an evaluation of party politics in different political issues, such as employment, education, child care and private enterprises. This is the first of the election studies to include a feeling thermometer, where the respondent has to position each of the political parties, as well as the party leaders, on a scale from -5 (dislikes very much) to +5 (likes very much). Since this study is the first that took place after a period of non-Social Democratic government, the respondent has to give a judgement over the two formations of Government (the three-party government 1976-1978 and the liberal government 1978-1979) which took place during this period, as well as an individual judgement of each of the parties in power and of the Social Democratic party as a opposition party. Two issues with special interest in this study are nuclear power and wage-earners´ investment fund.

Purpose:

Explain why people vote as they do and why an election ends in a particular way. Track and follow trends in the Swedish electoral democracy and make comparisons with other countries.

The Swedish election study 1979 was carried out in connection with the general election in September. Many of the questions are replications of questions asked in previous election studies. In this study the respondents specifies for each political party what they appreciates and what they dislikes with the party´s policy. There is also an evaluation of party politics in different political issues, such as employment, education, child care and private enterprises. This is the first of the election studies to include a feeling thermometer, where the respondent has to position each of the political parties, as well as the party leaders, on a scale from -5 (dislikes very much) to +5 (likes very much). Since this study is the first that took place after a period of non-Social Democratic government, the respondent has to give a judgement over the two formations of Government (the three-party government 1976-1978 and the liberal government 1978-1979) which took place during this period, as well as an individual judgement of each of the parties in power and of the Social Democratic party as a opposition party. Two issues with special interest in this study are nuclear power and wage-earners´ investment fund.

Syfte:

Förklara varför väljare röstar som de gör och varför val slutar som de gör. Spåra och följa trender i svensk valdemokrati och göra jämförelser med utvecklingen i andra länder.
Svensk valundersökning 1979
VU79
Keywords: elections; val; mass media; massmedia; occupations; yrken; participation; deltagande; politics; politik; public sector; offentlig sektor; social mobility; social rörlighet; ethics; etik; energy; energi; environment; miljö; voting intention; röstavsikt; voting; röstning; parliamentary elections; riksdagsval; political interest; politiskt intresse; political behaviour; politiskt beteende; party identification; partiidentifikation; political allegiance; politisk anhängare; political participation; politiskt deltagande; internal politics; inrikespolitik; political parties; politiska partier; illegal drugs; illegal drog; electoral issues; valfrågor; trade unions; fackföreningar; gender role; könsroll; organizations; organisationer; political attitudes; politiska åsikter; minority groups; minoritetsgrupp; CORS; CORS; Media; Media; Political behaviour and attitudes; Politiska beteenden och attityder; Elections; Val; Government, political systems and organisations; Regering, politiska system och organisationer; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap